Interventional management of hyperhidrosis in secondary care: a systematic review. (1st September 2018) - Wade, R.; Llewellyn, A.; Jones‐Diette, J.; Wright, K.; Rice, S.; Layton, A.M.; Levell, N.J.; Craig, D.; Woolacott, N.
Summary: Background: Hyperhidrosis is uncontrollable excessive sweating, which occurs at rest, regardless of temperature. The symptoms of hyperhidrosis can significantly affect quality of life. Objectives: To undertake a systematic review of the clinical effectiveness and safety of treatments available in secondary care for the management of primary hyperhidrosis. Methods: Fifteen databases (including trial registers) were searched to July 2016 to identify studies of secondary‐care treatments for primary hyperhidrosis. For each intervention randomized controlled trials (RCTs) were included where available; where RCT evidence was lacking, nonrandomized trials or large prospective case series were included. Outcomes of interest included disease severity, sweat rate, quality of life, patient satisfaction and adverse events. Trial quality was assessed using a modified version of the Cochrane Risk of Bias tool. Results were pooled in pairwise meta‐analyses where appropriate, otherwise a narrative synthesis was presented. Results: Fifty studies were included in the review: 32 RCTs, 17 nonrandomized trials and one case series. The studies varied in terms of population, intervention and methods of outcome assessment. Most studies were small, at high risk of bias and poorly reported. The interventions assessed were iontophoresis, botulinum toxin (BTX) injections, anticholinergic medications, curettage and newer energy‐based technologies that damage the sweat gland. Conclusions: The evidence for the effectiveness and safety of treatments for primary hyperhidrosis is limited overall, and few firm conclusions can be drawn. However, there is moderate‐quality evidence to support the use of BTX for axillary hyperhidrosis. A trial comparing BTX with iontophoresis for palmar hyperhidrosis is warranted.